1973
DOI: 10.1097/00132586-197304000-00016
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Tubocurarine and Alcuronium on Suxamethonium-Induced Changes in Cardiac Rate and Rhythm

Abstract: The effect of prior administration of tubocurarine ( 5 mg) or alcuronium ( 3 mg) on changes in cardiac rate and rhythm caused by the second dose of suxamethonium ( 1 mg/kg) during halothane-nitrous oxide-oxygen anaesthesia was studied in 60 patients. Tubocurarine and, particularly alcuronium were found to prevent bradyarrhythmias caused by the second dose of suxamethonium. These non-depolarizing relaxants had a moderate stabilizing action on the cardiac rhythm also during intubation and the commencement of art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
3

Year Published

1977
1977
1983
1983

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
1
3
3
Order By: Relevance
“…MATHIAS et al (1970) and KARHUNEN et al (1 972) found that prior administration of small doses of the non-depolarizing muscle-relaxants tubocurarine, alcuronium, c-toxiferine and pancuronium protected against these arrhythmias. This difference between our results with gallamine and the results of MATHIAS et al (1970) and KARHUNEN et al (1972) with the other non-depolarizing muscle-relaxants can, of course, be explained assuming gallamine to have a lesser ability than the other relaxants to prevent the bradyarrhythmias. However, the studies of MATHIAS et al (1970) and KARHUNEN et al (1972) are not directly comparable with the present study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…MATHIAS et al (1970) and KARHUNEN et al (1 972) found that prior administration of small doses of the non-depolarizing muscle-relaxants tubocurarine, alcuronium, c-toxiferine and pancuronium protected against these arrhythmias. This difference between our results with gallamine and the results of MATHIAS et al (1970) and KARHUNEN et al (1972) with the other non-depolarizing muscle-relaxants can, of course, be explained assuming gallamine to have a lesser ability than the other relaxants to prevent the bradyarrhythmias. However, the studies of MATHIAS et al (1970) and KARHUNEN et al (1972) are not directly comparable with the present study.…”
Section: Discussioncontrasting
confidence: 99%
“…This difference between our results with gallamine and the results of MATHIAS et al (1970) and KARHUNEN et al (1972) with the other non-depolarizing muscle-relaxants can, of course, be explained assuming gallamine to have a lesser ability than the other relaxants to prevent the bradyarrhythmias. However, the studies of MATHIAS et al (1970) and KARHUNEN et al (1972) are not directly comparable with the present study. In the study of KARHUNEN et al (1972), atropine 0.01 mg/kg (and pethidine 1 mg/kg) were given intramuscularly 30 min before anaesthesia, and the patients were intubated.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The incidence was highest in the pancuronium group, whereas in the alcuronium group only one patient showed a marked change in cardiac rhythm. This is in agreement with the results of KARHUNEN et al (1972), who found that d-tubocurarine and alcuronium pretreatments had a moderate stabilizing action on the cardiac rhythm during intubation. On the other hand, MATHIAS et al (1970) showed that bradycardia caused by a second dose of suxamethonium in man can be prevented in the same manner by d-tubocurarine, alcuronium and pancuronium.…”
Section: Discussionsupporting
confidence: 93%
“…MARTIN (1958) and BULLOUGH (1959) were the first to report that intermittent injections of suxamethonium in adults may provoke serious bradycardia. Several methods have been proposed to prevent this bradycardia : for example, the preanaesthetic administration of atropine or a small dose of a nondepolarizing muscle-relaxant (LEIGH et al 1957, LUPPRIAN & CHURCHILL-DAVIDSON 1960, KARHUNEN et al 1972. We have shown previously, however, that preanaesthetic intravenous injection of atropine before halothane inhalation anaesthesia does not protect against severe bradycardia following the second dose of suxamethonium, unless doses of atropine are used which cause potentially dangerous tachycardia (VIBY-MOGENSEN et al 1976).…”
mentioning
confidence: 99%